Minimum ignition energies and laminar burning velocities of ammonia, HFO-1234yf, HFC-32 and their mixtures with carbon dioxide, HFC-125 and HFC-134a - Sadaghiani, M.S.; Arami-Niya, Arash; Zhang, D.; Tsuji, T.; Tanaka, Y.; Seiki, Y.; May, E.F. (2021)
© 2020 Elsevier B.V. Given the safety issues associated with flammability characteristics of alternative environmentally-friendly refrigerants, it is vital to establish measurement systems to accurately analyse the flammability of these mildly flammable refrigerants. In this study, we used a customised Hartmann bomb analogue to measure the minimum ignition energy (MIE) and laminar burning velocity (BV) for refrigerant/air mixtures of pure ammonia (R717), R32, R1234yf and mixtures of R32 and R1234yf with non-flammable refrigerants of R134a, R125 and carbon dioxide (R744). The MIEs of R717, R32, and R1234yf were measured at an ambient temperature of 24 °C to be (18.0 ± 1.4), (8.0 ± 1.5) and (510 ± 130) mJ at equivalence ratios of 0.9, 1.27 and 1.33, respectively. Adding the non-flammable refrigerants R134a, R125 and R744 along with R32 at volumetric concentrations of 5% each to R1234yf reduced the latter compound's flammability and increased its MIE by one order of magnitude. The laminar burning velocities of pure R717 and R32 were measured at an equivalence ratio of 1.1 using the flat flame method and found to be 8.4 and 7.4 cm/s, respectively. Adding 5% R1234yf to R32 decreased the laminar burning velocity by 11%, while a further 5% addition of R1234yf resulted in a decrease of over 30% in the laminar burning velocity.